Government of Meghalaya Annual Plan 2009-2010 Draft Proposals - Planning Commission (Planning Commission, 2009)
Meghalaya became an Autonomous State within the State of Assam on 2nd April, 1970 comprising two erstwhile districts of Assam, viz. the United Khasi & Jaintia Hills District and the Garo Hills District. It was upgraded to a full fledged State with effect from 21st January, 1972. The State, with a geographical area of 22,429 Sq. Kms, has 7 Districts viz. (i) East Khasi Hills District (ii) West Khasi Hills (iii) Jaintia Hills (iv) Ri-Bhoi (v) West Garo Hills (vi) East Garo Hills and (vii) South Garo Hills and 39 C&RD Blocks. It is strategically located in the North-East between 25° 5” and 26° 10” North Latitudes and between 98° 47” and 97° 47” East Longitudes, bounded by Bangladesh on the South as well as partly on the West (international boundary about 443 Km) and surrounded on the other sides by Assam.
Planning Department